Avaliação neuropsicológica e dos marcadores inflamatórios nos pacientes com epilepsia - Arend, Josi (2015)
The epilepsy is a neurological disorder manifested by recurrent unprovoked seizures, resulting in harmful effects on the patients. Epileptic seizures are generated from hypersincronic abnormal discharges of neurons, eventually resulting in irreversible damage. The consequences involve damages in the neurobiological, neurochemical, cognitive and psychological scopes. As a result, the objective of this study was to investigate the cognitive function (NEUPSILIN test), depression score (Hamilton Rating Scale) and inflammatory markers (TNF, IL1β, AChE), cell death (caspase 3) and DNA damage (PicoGreen) in epileptic patients, compared to individuals without the disease. The results showed significant memory damages in patients with epilepsy, as well as a high depression score. The inflammatory markers, cell death and DNA damage also were showed high. In addition, there was not observed significant correlation when were compared the seizures duration with memory impairment and depression score. There was also no significant correlation when comparing the depression scores and the enzyme acetylcholinesterase activity with memory impairment. In this way, the results of this study suggest that the neurophysiological changes caused by the epilepsy may be responsible for the memory damages and higher rates of depression in patients. Furthermore, it can be suggested that the seizures contribute to the development of neuroinflammation, releasing inflammatory mediators and, by this way, initiating a apoptotic cascade that culminates in the DNA damage.